EXAMINING THE EXTERNAL DEBT CRISIS IN INDONESIA FROM ISLAMIC PERSPECTIVE - Khonsa Tsabita (Faculty of Islamic Economics and Business, Universitas Islam Negeri Ar-Raniry, 2018)
One of major economic problems particularly in developing countries is external debt crisis. Several developing countries including Indonesia have paid their external debt more than total fund they have received from developed countries. Moreover, the indebted country has to pay the interest every year which the amount keeps accruing. Debt is the main causes of poverty since most of them are “unjust” debt. Islam discourages Muslims to depend their lives on borrowing money, including at the state level. This research attempts to scrutinize the issue of external debt crisis and try to come out with a solution to the problem of the external debt crisis in Indonesia from Islamic perspective. This paper is using a qualitative analysis approach and collecting external debt data from the Central Bank of Indonesia and the World Bank. Findings indicate that the current system on managing external debt crisis in Indonesia has not been successful and need to be examined from different frameworks. Overall, this paper contributes to literatures on the debt crisis and provides some alternative solutions to government to manage the external debt crisis.===============================================Pengkajian Krisis Utang Luar Negeri Di Indonesia Dari Perspektif Islam - Salah satu persoalan ekonomi utama khususnya di negara berkembang adalah krisis utang luar negeri. Negara-negara berkembang termasuk Indonesia membayar utang luar negeri mereka kepada negara-negara maju melebihi total dana yang diterima. Selain itu, negara-negara tersebut juga harus membayar bunga setiap tahun yang jumlahnya terus meningkat. Utang merupakan penyebab utama kemiskinan disebakan sebagian besar dari utang bersifat